Preventing homelessness among women prison leavers in Wales. (November 2022) - Gorden, Caroline; Lockwood, Kelly; Madoc-Jones, Iolo; Dubberley, Sarah; Hughes, Caroline; Washington-Dyer, Karen; Wilding, Mark A; Ahmed, Anya
Under the Housing (Wales) Act 2014, prison leavers are among those who are no longer considered a priority need. This article draws on interviews conducted with 17 women prison leavers and 10 professionals that formed part of a Welsh Government funded evaluation of homelessness services to adults in the secure estate (Madoc-Jones et al., 2018). The findings in this study lend support to previous research that indicates women who come into contact with the criminal justice system often have multiple and complex needs. The findings of the study support the need for gender-specific services and more availability of supported accommodation to ensure the effective resettlement of women prison leavers.